Without Asking. Language and Animality in Emmanuel Levinas - Cervato, Giulia (Scenari, 2024)
The animal question is one of the most significant points of the critical comparison between Emmanuel Levinas and Jacques Derrida. In The Animal That Therefore I Am, the latter blames the former for relegating animality to a secondary role. In Derrida’s perspective, Levinas renounces identifying the animal as a wholly Other and thus remains, despite his claims, a carnophallogocentric thinker. The main contention of this paper is that Levinas, as the perfect heir of the Greco-Jewish tradition, is not able to articulate the ethical relationship outside of the linguistic model. Therefore, he cannot grant animals a primary role and, when they enter the ethical discussion, they must always be anthropomorphized. The only exception to this model is represented by Levinas’ analysis of a Biblical passage. As Levinas underlines, in this context, the matriarch Rebekah waters Abraham’s servant’s camels because they cannot ask for it, that is, precisely because they lack linguistic expressivity. Despite not being fully seized by Levinas, these hints of the biblical text could widen the applicational context of Levinasian ethics towards animals and properly pave the way for an ethics of difference. Moreover, in a paradoxical counterpoint, following such hints to the end and amplifying the unexpressed meanings of the Biblical text may lead to adhering to that prophetic dimension indicated by Levinas as the highest characteristic of human language itself.